2016
DOI: 10.1080/14760584.2016.1203262
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine development for syphilis

Abstract: Introduction Syphilis, caused by the spirochete Treponema pallidum subspecies pallidum, continues to be a globally prevalent disease despite remaining susceptible to penicillin treatment. Syphilis vaccine development is a viable preventative approach that will serve to complement public health-oriented syphilis prevention, screening and treatment initiatives to deliver a two-pronged approach to stemming disease spread worldwide. Areas covered This article provides an overview of the need for development of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 106 publications
0
51
0
2
Order By: Relevance
“…To date, developed vaccines against T. pallidum have included an inactivated vaccine, live attenuated vaccines, recombinant protein vaccines and DNA vaccines 7 9 . γ-Irradiated T. pallidum , which is an attenuated syphilis spirochete, has been used as an attenuated vaccine to induce a protective antibody response against T. pallidum in vivo, although the relative efficacy of this vaccine has not been well defined in animal trials 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, developed vaccines against T. pallidum have included an inactivated vaccine, live attenuated vaccines, recombinant protein vaccines and DNA vaccines 7 9 . γ-Irradiated T. pallidum , which is an attenuated syphilis spirochete, has been used as an attenuated vaccine to induce a protective antibody response against T. pallidum in vivo, although the relative efficacy of this vaccine has not been well defined in animal trials 8 .…”
Section: Introductionmentioning
confidence: 99%
“…More seriously, T. pallidum can permeate both the placental and blood–brain barriers and increases the risk of acquiring and transmitting human immunodeficiency virus (HIV) 15 17 . Therefore, effective syphilis vaccine development needs to target treponemes within the vasculature to inhibit T. pallidum seeding into a wide variety of tissues and organs 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Vaccine development efforts vary by specific STI. HSV and CT vaccine candidates are in clinical trials, while NG and syphilis vaccine candidates are still in preclinical development [60, 61]. Notably, a recent study showed a serogroup B meningococcal vaccine to be 31% effective against NG, the first instance of a protective vaccine against NG [62, 63].…”
Section: Future Directionsmentioning
confidence: 99%
“…Это обусловлено тем, что такая вакцина должна либо устранять, либо как минимум снижать вероятность передачи возбудителя от человека к человеку. Также необходимо, чтобы вакцина предотвращала распространение возбудителя в организме инфицированного человека, рецидивы заболевания, персистирование возбудителя и латентное течение инфекции [8].…”
Section: сифилисunclassified
“…Возможными мишенями для вакцин против сифилиса являются отдельные подгруппы белков, относящихся к семейству Tpr (T. pallidum repeat) (нацеливание на восприимчивость к инфекции и персистирование возбудителя), и белок Tp0751 (трепонемный белок паллилизин, относящийся к адгезинам) (нацеливание на распространение возбудителя) [8,10]. Новым подходом к созданию вакцины было использование инактивированной Borrelia burgdorferi в качестве эффективного носителя для доставки антигенов и индукции специфического ответа макроорганизма на антигены T. pallidum, экспрессируемые генами tp0897 (tprK) и tp0435 [11].…”
Section: сифилисunclassified